The link between alterations in circadian rhythms and lipid metabolism in bipolar disorder: the hypothesis of lipid droplets - Ana Catarina Pereira; Laura Serrano-Cuñarro; Maria Teresa Cruz; Cláudia Cavadas; Cláudia Maria Fragão Pereira (Brazilian Journal of Psychiatry)
Bipolar disorder (BD) is a neuropsychiatric illness characterized by recurrent episodes of mania and depression, leading to significant cognitive and functional impairments, psychiatric and metabolic comorbidities, and substantial healthcare costs. The complex nature and lack of specific biomarkers for BD make it a daily challenge for clinicians. Therefore, advancing our understanding of BD pathophysiology is essential to identify novel diagnostic biomarkers and potential therapeutic targets. Although its neurobiology remains unclear, circadian disruption and lipid alterations have emerged as key hallmarks of BD. Lipids are essential components of the brain and play a critical role in regulating synaptic activity and neuronal development. Consequently, alterations in brain lipids may contribute to the neuroanatomical changes and reduced neuroplasticity observed in BD. Lipid droplets, which regulate the storage of neutral lipids, buffer the levels of toxic lipids within cells. These dynamic organelles adapt to cellular needs, and their dysregulated accumulation has been implicated in several pathological conditions. Notably, lipid droplets and different classes of lipids exhibit rhythmic oscillations throughout the 24-hour cycle, suggesting a link between lipid metabolism, circadian rhythms, and lipid droplets. In this review, we explore the impairment of circadian rhythms and lipid metabolism in BD and present evidence that circadian clocks regulate lipid droplet accumulation. Importantly, we propose the “hypothesis of lipid droplets for BD,” which posits that impaired lipid metabolism in BD is closely linked to alterations in lipid droplet homeostasis driven by circadian clock disruption.